2021
DOI: 10.31009/feast.i4.06
|View full text |Cite
|
Sign up to set email alerts
|

Shifted indexicals in Hong Kong Sign Language with(-out) role shift

Abstract: This study investigates shifted indexicals in Hong Kong Sign Language (hereafter HKSL). In elicited data, shifted indexicals are attested in utterances with and without attitude role shift. The data further show that attitude role shift has both quotation-like and nonquotation-like characteristics, leading to the conclusion that neither of the two major accounts for role shift, the Demonstration Account by Davidson (2015) or the Indexical Shifting Operator Account by Schlenker (2017b, 2017a) suffices to fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…However, previous studies on Catalan SL (Quer 2011), German SL (Herrmann and Steinbach 2012b), Russian SL (Kimmelman and Khristoforova 2018), and Hong-Kong SL (Gan 2021) have shown that RS-NMMs are neither necessary nor sufficient for the indexicals to shift. In fact, these studies reveal that indexicals within the scope of RS-NMMs do not always 'shift together'.…”
Section: Introductionmentioning
confidence: 83%
“…However, previous studies on Catalan SL (Quer 2011), German SL (Herrmann and Steinbach 2012b), Russian SL (Kimmelman and Khristoforova 2018), and Hong-Kong SL (Gan 2021) have shown that RS-NMMs are neither necessary nor sufficient for the indexicals to shift. In fact, these studies reveal that indexicals within the scope of RS-NMMs do not always 'shift together'.…”
Section: Introductionmentioning
confidence: 83%